Promoting learners' conceptual understanding of electrostatics through use of practical activities in conjunction with prior knowledge of lightning : a case study - Maselwa, Matole Reuben (Rhodes University, Faculty of Education, Department of Education, 2004)
The research presented in this thesis is situated within an interpretivist paradigm. Within this paradigm, a qualitative case-study research approach was adopted. This seemed most appropriate in my research project since the main focus is on elicitation of prior knowledge and incorporation of such knowledge into 'hands-on' and 'minds-on' practical activities with a view to improving conceptual development. For the purposes of this research project, I designed an interactive teaching and learning unit in electrostatics as an attempt to put into practice a learner-centred approach. This approach, in my view, is in line with the new curriculum in South Africa. The emerging central theme of this thesis is the notion of active participation by learners during teaching and learning. This study was carried out over a period of two years and involved my grade 9 learners, who participated voluntarily. The research process documented in this thesis has been conceptualised into two phases. Phase one was concerned with the elicitation of learners' prior knowledge around lightning. In phase two, learners were engaged in 'hands-on' and 'minds-on' practical activities, and key concepts were identified to ensure conceptual development. The data was collected using a variety of data collection tools, namely: focus group interviews, follow-up whole-class semi-structured interviews, worksheets, videotaped lessons and photographs. The analysis of data revealed that learners come to class with prior knowledge concerning lightning. Within this prior knowledge it was found that there were both 'scientific' and 'non-scientific' concepts. The identification of key concepts during practical activities was found to be very useful in promoting learning. However, the incorporation of prior knowledge into practical activities posed a challenge and needs further research. iv This research study also highlights some insights into some of the complexities of elicitation and incorporation of learners' prior knowledge, and conceptual development in science classrooms. It also demonstrates the challenges and possibilities during teaching and learning as well as the realities of the demands of the new curriculum and OBE in South Africa, in particular, in historically disadvantaged schools
Keywords: Electrostatics -- Study and teaching -- Case studies; Science -- Study and teaching -- Case studies; Lightning -- Study and teaching -- Case studies